2017
DOI: 10.29252/pbr.3.2.39
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm potential of Lactobacillus plantarum spp. cell free supernatant (CFS) against multidrug resistant bacterial pathogens

Abstract: Biofilm formation is a major determinant factor in development of bacterial infections. In addition, bacteria embedded in a biofilm are more resistant to antimicrobials and thus the ability of bacteria to persist and grow in a biofilm seems to be the major factor for pathogenesis and therapeutic failure. In the current study, a Lactobacillus plantarum spp was isolated from Siahmazgi cheese, traditional cheese of Guilan province, Iran, and was identified using morphological, biochemical and molecular identifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Similarly, the pH neutralized CFS of L. plantarum, L. helveticus, Propionibacterium acidilactici, and E. faecium revealed a substantial reduction in biofilm formation of S. aureus CMCC26003 and E. coli CVCC230 [133]. To overcome biofilm-forming multi-drug resistant superbugs (P. aeruginosa, S. aureus, and E. coli), investigators have used CFS of LAB for the successful mitigation of pathological conditions [134,135]. Therefore, these findings suggested that the CFS of LAB may act as bio-liquid-detergent that reduces the adhesion and biofilm formation of pathogens to the various surfaces (biotic and abiotic surfaces).…”
Section: Cell-free Supernatant and Soluble Factorsmentioning
confidence: 99%
“…Similarly, the pH neutralized CFS of L. plantarum, L. helveticus, Propionibacterium acidilactici, and E. faecium revealed a substantial reduction in biofilm formation of S. aureus CMCC26003 and E. coli CVCC230 [133]. To overcome biofilm-forming multi-drug resistant superbugs (P. aeruginosa, S. aureus, and E. coli), investigators have used CFS of LAB for the successful mitigation of pathological conditions [134,135]. Therefore, these findings suggested that the CFS of LAB may act as bio-liquid-detergent that reduces the adhesion and biofilm formation of pathogens to the various surfaces (biotic and abiotic surfaces).…”
Section: Cell-free Supernatant and Soluble Factorsmentioning
confidence: 99%
“…CFS from L. plantarum disrupted preformed biofilms of the tested pathogen bacteria by 37% to 46.6%. The antibiofilm compound appeared to be sensitive to proteinase K activity since after the CFS was treated with this enzyme, and the antibiofilm activity was lost (Zamani et al., 2017). El‐Mokhtar et al.…”
Section: Antimicrobial Activity Of Cfss In Vitromentioning
confidence: 99%
“…For coaggregation, the results illustrated that the percentages of coaggregation after 24 h incubation were higher compared to 4 h. Similarly, Algburi et al [38] reported high levels of coaggregation of pathogenic P. mirabilis, isolated from urinary tract infections, with B. amyloliquefaciens B-1895 and B. subtilis KATMIRA1933 after 24 h incubation. Coaggregation of probiotic strains with pathogenic bacteria is indicative of competition between the two bacterial species on the attached surfaces, which may play an important role in inhibiting biofilm formation [39].…”
Section: Discussionmentioning
confidence: 99%
“…The CFS obtained from probiotic species contains various biologically active compounds, including exopolysaccharides, proteins, biosurfactants, and digestive enzymes. These substances are associated with the inhibition or destruction of the preformed biofilm [39].…”
Section: Discussionmentioning
confidence: 99%